Pengaruh Sense of Humor terhadap Keakraban Siswa dalam Bergaul di SMP Negeri 22 Kota Jambi - Galuh Ayu Pramudita; Akmal Sutja; Freddi Sarman (Departement of Mathematics Education, 2023)
In everyday life humans have various ways of establishing communication between one another. This activity is called associating. Humans have their own art in associating, one of which is by using a sense of humor or the sensitivity of humor. The art of socializing in the form of a sense of humor is used whose purpose is to bring the individual to be familiar with other individuals and their environment. This also applies in the school environment. Students with a good sense of humor will tend to make friends easily and have a good impact on familiarity with one another and vice versa. The purpose of this study was to determine the quality of the sense of humor and the quality of students' intimacy in socializing and to find the influence between the two. This type of research is quantitative with ex post facto method. Data collection techniques used in the form of observation, interviews and questionnaires. The validity of the data is proven through percentage test, hypothesis test and simple regression. Data analysis uses techniques that are implemented from reduction, presentation and conclusion.